2012
DOI: 10.2135/cropsci2012.03.0175
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Mapping Analysis of Bread‐Making Quality Traits in Spring Wheat

Abstract: In this study we assess the genetic architecture of bread-making quality traits in spring wheat {Triticum aestivum L.). A mapping population derived from BR34 and 'Grandin' was used to measure 20 end-use quality traits including six kernel, seven milling and flour, four dough mixing strength, and three bread-making traits. A total of 31 quantitative trait loci (QTL) significantly associated with all but two traits were identified. These QTL were clustered in five chromosomal regions, namely IBS, 1DL, 4BL, 5BL,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 80 publications
6
48
4
Order By: Relevance
“…Mixograph traits that reflected optimum dough development and stability have shown correlations among themselves and with grain, flour and baking quality traits in earlier reports (Groos et al, 2007;Mann et al, 2009;Simons et al, 2012;Tsilo et al, 2011;Zhang et al, 2008). Further, detection of QTL clusters for those characters suggested common or closely linked underlying loci.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Mixograph traits that reflected optimum dough development and stability have shown correlations among themselves and with grain, flour and baking quality traits in earlier reports (Groos et al, 2007;Mann et al, 2009;Simons et al, 2012;Tsilo et al, 2011;Zhang et al, 2008). Further, detection of QTL clusters for those characters suggested common or closely linked underlying loci.…”
Section: Introductionmentioning
confidence: 85%
“…In the previous studies, majority of the QTLs for dough and bread quality parameters were detected in single or few of the tested environments which suggested the impact of genotype  environment interactions (GEI) on these traits (Bordes et al, 2011;Mann et al, 2009;Simons et al, 2012;Tsilo et al, 2011). The analyses of variance (ANOVA) in previous reports indicated substantial unexplained variance in addition to the G and E effects that in part could be due to the underlying GEI (Ma et al, 2005;Tsilo et al, 2011).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Only a single QTL cluster on chromosome 5B showed co-location for LV and DRT. In many of the previous studies, large number of DRT and BMQ QTLs were detected in single environments (Mann et al 2009 ;Tsilo et al 2011 ;Li et al 2012 ;Simons et al 2012 ) and stable QTLs were very few, which often co-located with HMW glutenin loci (Mann et al 2009 ;Tsilo et al 2011 ). Examining their specifi city to individual locations and pattern of detection across years within a location can help reveal their responses to GEI.…”
Section: Clustering and Location-specifi City Of Bmq And Drt Qtlsmentioning
confidence: 99%
“…In addition, QTL clusters mainly for GPC, SV and DRT (Li et al ) and for DRT and LV (Mann et al 2009 ;Tsilo et al 2011 ;Simons et al 2012 ) suggested that as the traits are correlated, they could be controlled by common QTLs. But it needs to be noted that the HMW glutenin loci Glu-B1 or Glu-D1 often showed overlap with the largest of such clusters for DRT and LV and suggested that extensive studies to identify novel loci on other chromosomes are necessary for further improvement of wheat quality.…”
Section: Clustering and Location-specifi City Of Bmq And Drt Qtlsmentioning
confidence: 99%